(untitled) (Veterinary Science, 2017)
The objective of this work was to evaluate the efficiency to use atmospheric air as a substitute of oxygen in anaesthetic dogs with halothane. The work was carried out in two groups of fife animals each using either oxygen or compressed air. Physiologic parameters such as clinica signs and arterial blood analysed were done. To evaluate the breath efficiency blood arterial samples were taken at 30, 60 and 90 minutes trough measurement of the partial pressure of PCO2, PO2 and pH. Under the present condition the inhalatory anaesthesia with halothane and assisted breath using atmospheric air with quirurgic time until 90 minutes shown comparative parameter as that using medicinal oxygen.